2015
DOI: 10.1111/1462-2920.12825
|View full text |Cite
|
Sign up to set email alerts
|

Effects, but no interactions, of ubiquitous pesticide and parasite stressors on honey bee (Apis mellifera) lifespan and behaviour in a colony environment

Abstract: SummaryInteractions between pesticides and parasites are believed to be responsible for increased mortality of honey bee (Apis mellifera) colonies in the northern hemisphere. Previous efforts have employed experimental approaches using small groups under laboratory conditions to investigate influence of these stressors on honey bee physiology and behaviour, although both the colony level and field conditions play a key role for eusocial honey bees. Here, we challenged honey bee workers under in vivo colony con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 78 publications
5
42
2
Order By: Relevance
“…The observed infection loads of individual bees were significantly higher for L. passim compared to N. ceranae , and are well within the limits of previous reports for foraging bees (Bourgeois et al., 2010; Ravoet et al., 2013, 2015; Retschnig, Neumann, & Williams, 2014; Retschnig et al., 2015). Despite the observed high infection loads, there were no significant differences between the infection loads of both parasites in single‐ or double‐infected hosts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed infection loads of individual bees were significantly higher for L. passim compared to N. ceranae , and are well within the limits of previous reports for foraging bees (Bourgeois et al., 2010; Ravoet et al., 2013, 2015; Retschnig, Neumann, & Williams, 2014; Retschnig et al., 2015). Despite the observed high infection loads, there were no significant differences between the infection loads of both parasites in single‐ or double‐infected hosts.…”
Section: Discussionmentioning
confidence: 99%
“…As laboratory tests may not necessarily reflect field conditions (Retschnig et al., 2015), we took advantage of natural occurring infections of honey bee hosts with N. ceranae and L. passim in the field to test the following hypotheses: If the two parasites significantly interact with each other, we expect less or more individual hosts infected with both parasites compared to a random distribution. Likewise, infection loads of bees with one parasite alone should differ from those bees infected with both parasites.…”
Section: Introductionmentioning
confidence: 99%
“…Pettis et al (2012) reported a higher infection of Nosema species in honeybees exposed to neonicotinoids, while Aufauvre et al (2012) demonstrated the impact of multiple exposure to both parasites and pesticides. However, under field conditions, Retschnig et al (2015) found no interactions between N. ceranae and neonicotinoid pesticides, and therefore, more studies under natural situations are necessary before definitive conclusions can be made.…”
Section: Pesticidesmentioning
confidence: 95%
“…As mentioned earlier, when multiple stresses (such as pesticides and parasites) are combined, the outcome for individual bees, colonies and populations is predicted to be negative (Bryden et al, 2013;Vanbergen et al, 2013;Goulson et al, 2015). Indeed, studies supporting this idea are on the increase (Alaux et al, 2010;Vidau et al, 2011;Fauser-Misslin et al, 2014;Retschnig et al, 2014;Doublet et al, 2015; but see Retschnig et al, 2015), but significant knowledge gaps relating the effects of potential ecologically relevant threats to diverse pollinators persist (Lundin et al, 2015).…”
Section: Introductionmentioning
confidence: 93%